Lung type 3 innate lymphoid cells respond early following Mycobacterium tuberculosis infection - Shibali Das; Kuldeep Singh Chauhan; Mushtaq Ahmed; Sadia Akter; Lan Lu; Marco Colonna; Shabaana A. Khader (mBio, 2024)
ABSTRACTTuberculosis is the leading cause of death due to an infectious disease worldwide. Innate lymphoid type 3 cells (ILC3s) mediate early protection during Mycobacterium tuberculosis (Mtb) infection. However, the early signaling mechanisms that govern ILC3 activation or recruitment within the lung during Mtb infection are unclear. scRNA-seq analysis of Mtb-infected mouse lung innate lymphoid cells (ILCs) has revealed the presence of different clusters of ILC populations, suggesting heterogeneity. Using mouse models, we show that during Mtb infection, interleukin-1 receptor (IL-1R) signaling on epithelial cells drives ILC3 expansion and regulates ILC3 accumulation in the lung. Furthermore, our data revealed that C-X-C motif chemokine receptor 5 (CXCR5) signaling plays a crucial role in ILC3 recruitment from periphery during Mtb infection. Our study thus establishes the early responses that drive ILC3 accumulation during Mtb infection and points to ILC3s as a potential vaccine target.IMPORTANCETuberculosis is a leading cause of death due to a single infectious agent accounting for 1.6 million deaths each year. In our study, we determined the role of type 3 innate lymphoid cells in early immune events necessary for achieving protection during Mtb infection. Our study reveals distinct clusters of ILC2, ILC3, and ILC3/ILC1-like cells in Mtb infection. Moreover, our study reveal that IL-1R signaling on lung type 2 epithelial cells plays a key role in lung ILC3 accumulation during Mtb infection. CXCR5 on ILC3s is involved in ILC3 homing from periphery during Mtb infection. Thus, our study provides novel insights into the early immune mechanisms governed by innate lymphoid cells that can be targeted for potential vaccine-induced protection.